2018
DOI: 10.1101/508275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bi-clustering based biological and clinical characterization of colorectal cancer in complementary to CMS classification

Abstract: 19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Bioinformatics, 36(4), 1143-1149. https://doi.org/10.1093/bioinformatics/btz692 scRNA-Seq data can further facilitate the discovery of gene signatures of specific cell types, and most importantly, the identified FGMs can be used to study the complex interactions among individual cells in response to certain stimuli, that is, cell type prediction. Our recent identification of FGMs specific to a subset of patients revealed biological characteristics of different disease subtypes and alternative drug resistance mechanisms in colorectal cancer (Cao, et al, 2018). In addition, we have demonstrated the correspondence between the cell sample-specific FMGs and gene coregulation modules in scRNA-Seq data (Wan, et al, 2018).…”
Section: Introductionmentioning
confidence: 73%
“…Bioinformatics, 36(4), 1143-1149. https://doi.org/10.1093/bioinformatics/btz692 scRNA-Seq data can further facilitate the discovery of gene signatures of specific cell types, and most importantly, the identified FGMs can be used to study the complex interactions among individual cells in response to certain stimuli, that is, cell type prediction. Our recent identification of FGMs specific to a subset of patients revealed biological characteristics of different disease subtypes and alternative drug resistance mechanisms in colorectal cancer (Cao, et al, 2018). In addition, we have demonstrated the correspondence between the cell sample-specific FMGs and gene coregulation modules in scRNA-Seq data (Wan, et al, 2018).…”
Section: Introductionmentioning
confidence: 73%
“…On the contrary, a transcriptomic study on human NCI-60 tumors showed that OGT expression is negatively correlated with FdUMP sensitivity, no correlation with 5-FU sensitivity was established ( 78 ). OGT was also identified in a cluster of co-expressed genes associated with 5-FU resistance in colorectal cancer (CRC) ( 79 ). Moreover, the 5-FU pathway actors SLC29A1 ( 80 ), TP ( 10 ), TK ( 81 , 82 ), and TS ( 34 ) are direct targets for O -GlcNAcylation ( Figure 2 ).…”
Section: Impact Of O -Glcnacylation On Response To...mentioning
confidence: 99%